Analysis and evaluation of the energy saving potential of the CO2 chemical absorption process. (December 2021) - Zheng, Yawen; He, Song; Gao, Lin; Li, Sheng
Highlights: Energy saving mechanisms of process upgrading and absorbent innovation are studied. A new thermodynamic angle for identifying energy saving potential is introduced. Energy saving potentials of various kinds of novel absorbents are assessed. Suggestions for future improvement of chemical absorption technology are provided. Abstract: Carbon Capture and Storage (CCS) plays an important role in dealing with global warming, while the high energy consumption of CO2 separation is the critical gap interfering with the development and deployment of CCS. The aim of this work is to identify the energy saving potentials of different CO2 separation technical measures from the level of thermodynamic principles. The energy saving mechanism of these two technical measures is investigated through analysis of energy consumption and exergy destruction distributions and further disclosed by the Energy Utilization Diagram (EUD) method. The results indicate that the relative importance of absorbent innovation and process upgrading will change for emission sources with different CO2 concentrations. Absorbent innovation is more sensible for emission sources with higher CO2 concentrations, while the role of process upgrading will be enhanced for low-concentration sources. Moreover, absorbent innovation can affect the reboiler duty from the perspective of both energy quantity and energy quality, while process upgrading mainly affects the energy amount of the reboiler duty. Through comparison of diverse absorbents, the results indicate that the field is still in the key stage of absorbent innovation for current chemical absorption technology. Upon transition to lower reboiler (<2.5) duty and lower I AP (<1.5), process upgrading can be expected to be a more effective and faster way to save energy than absorbent innovation.